Otherness Within the Otherness: Discrimination of Muslim Female Prisoners in the Prison System of Habsburg Bosnia - Amila Kasumović (Tarih Dergisi)
The issues of the prison system of the Habsburg Monarchy and the treatment of its prisoners in the late 19th century have not been investigated in historiography. Historians did not pay attention to the treatment of female prisoners in Habsburg’s penal practices in the late 19th and early 20th centuries. Based on archival records, the article aims to fill this lacuna in the historiography of the Habsburg Monarchy in order to demonstrate how the Habsburg administration in Bosnia either failed to accomplish much-needed reforms within the prison system or at least failed to achieve them in full, even though Habsburg officials promised to implement the Irish progressive system, the golden standard of the time. The article illustrates that the modern approach to imprisonment and the treatment of prisoners in accordance with the latest belief that time spent in prison could rehabilitate the prisoner was not correctly applied to long-term female prisoners in Bosnia, especially Muslim ones.